Answer:
a) 0≠ -10
b) x= -3
c)y= 0
Explanation:
a) 3-4x=-7-4x
![3-4x=-7-4x\\Adding \ 4x \ on \ both \ sides\\3-4x+4x=-7-4x+4x\\3-0=-7\\Adding \ -3\\3-0-3=-7-3\\0\\eq -10](https://img.qammunity.org/2021/formulas/mathematics/college/dp5110ttjfskkvv73au390ev36oj9pb14n.png)
So, this equation has no solution as both sides are not equal.
b)
![15-2x=-7x](https://img.qammunity.org/2021/formulas/mathematics/college/gbmgomnkyev4lw85sxu42nryn9jxz842g4.png)
Solving:
![15-2x=-7x\\Adding \ 2x \ on \ both \ sides\\15-2x+2x=-7x+2x\\15=-5x\\Divide \ both \ sides \ by -5\\x=-3](https://img.qammunity.org/2021/formulas/mathematics/college/936ii8n5ctemzurwh1pe9xluobeqwcuxnn.png)
So, this equation has one solution
c) 7(y-3)=6y-21
Solving:
![7(y-3)=6y-21\\7y-21=6y-21\\Adding \ -6y \ on \ both \ sides\\7y-21-6y=6y-21-6y\\y=-21+21\\y=0](https://img.qammunity.org/2021/formulas/mathematics/college/issnogu42u7vd21ve842v7c3ulwhow8z3s.png)
So, this equation has one solution.
1. Write equation with no solution. 3-4x=-7-4x (check solution of a)
2. Write equation with one solution. 7(y-3)=6y-21 (check solution of c)
3. Write equation with infinite solution. 2x + 3 = x + x + 3
solving:
2x+3=2x+3
2x-2x+3=3
3=3
When both sides are equal, the equation has infinite solutions.